2007
DOI: 10.1111/j.1365-2885.2007.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of halofuginone lactate on treatment and prevention of lamb cryptosporidiosis: an extensive field trial

Abstract: This study aimed to investigate the effects of halofuginone lactate (100 mug/kg BW) on treatment and prevention of cryptosporidiosis in lambs. It consisted of three field trials. The first trial was designed to assess the efficacy of halofuginone in treating lamb diarrhoea caused by cryptosporidiosis, and in preventing the disease, using two schemes; halofuginone given for seven and for three consecutive days respectively. Halofuginone was effective in the treatment of diarrhoea caused by cryptosporidiosis (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Nevertheless, the farm prevalence on the sheep (57.1%) and goat (50.0%) farms does suggest that Cryptosporidium is widespread and is a potential threat to the small ruminant population. In previous studies in Greece, Cryptosporidium has been associated with large outbreaks of diarrhoea in both sheep and goat flocks [14, 15, 37], similar to other major small ruminant rearing countries [6, 33]. …”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, the farm prevalence on the sheep (57.1%) and goat (50.0%) farms does suggest that Cryptosporidium is widespread and is a potential threat to the small ruminant population. In previous studies in Greece, Cryptosporidium has been associated with large outbreaks of diarrhoea in both sheep and goat flocks [14, 15, 37], similar to other major small ruminant rearing countries [6, 33]. …”
Section: Discussionmentioning
confidence: 82%
“…Cryptosporidiosis, which was initially diagnosed in this flock, has been reported as a possible cause of illthrift by some authors [10, 11]. Although our research group has not found any correlation of cryptosporidiosis, as an individual entity, with growth retardation in lambs [12] and, furthermore, the cryptosporidial infection initially present was eliminated following treatment with halofuginone lactate [10, 12, 13], the initial presence of cryptosporidiosis may have contributed to the severity of the umbilical infections and their sequelae.…”
Section: Discussionmentioning
confidence: 67%
“…Also, halofuginone at the recommended dose (0,1 mg kg −1 for seven consecutive days) seems to restraints cryptosporidial reproduction rate and improves the development of immunity in lambs (Causape et al, 1999;Giadinis et al, 2007).…”
Section: Halofuginone Lactatementioning
confidence: 99%